2018
DOI: 10.5194/wes-3-25-2018
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled simulations of offshore wind turbines with reduced rotor loads and aerodynamic damping

Abstract: Abstract. Decoupled load simulations are a computationally efficient method to perform a dynamic analysis of an offshore wind turbine. Modelling the dynamic interactions between rotor and support structure, especially the damping caused by the rotating rotor, is of importance, since it influences the structural response significantly and has a major impact on estimating fatigue lifetime. Linear damping is usually used for this purpose, but experimentally and analytically derived formulas to calculate an aerody… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This means that for every step to a new wind speed, the structure decays to a new equilibrium position. These "decays" allow an equivalent linear damping ratio to be extracted and the principle is based on the work done by Schløer et al (2016) and Schløer et al (2018). Schafhirt and Muskulus (2018) made a detailed analysis of this approach and found that although the aero-elastic damping process is not linear, it can be successfully modelled by a linear damping model.…”
Section: The Simplified Model: Qulafmentioning
confidence: 99%
“…This means that for every step to a new wind speed, the structure decays to a new equilibrium position. These "decays" allow an equivalent linear damping ratio to be extracted and the principle is based on the work done by Schløer et al (2016) and Schløer et al (2018). Schafhirt and Muskulus (2018) made a detailed analysis of this approach and found that although the aero-elastic damping process is not linear, it can be successfully modelled by a linear damping model.…”
Section: The Simplified Model: Qulafmentioning
confidence: 99%
“…This means that for every step to a new wind speed, the structure decays to a new equilibrium position. These "decays" allow an equivalent linear damping ratio to be extracted and the principle is based on the work done by Schløer et al (2016) and Schløer et al (2018). Schafhirt and Muskulus (2018) made a detailed analysis of this approach and found that although the aero-elastic damping process is not linear, it can be successfully modelled by a linear damping model.…”
Section: The Simplified Model: Qulafmentioning
confidence: 99%
“…Ref. [17] compared results obtained from a fully integrated simulation and those of a decoupled system accounting for linear aerodynamic damping. The results showed that even if the aerodynamic damping is nonlinear, it is possible to match the results of a fully coupled-or integrated-simulation if optimization of the damping ratios for different wind speeds is performed.…”
Section: Introductionmentioning
confidence: 99%
“…Both [16,17] focused on the decoupling of the wind turbine rotor from the support structure. However, that is not the only component of an offshore wind turbine that could be decoupled.…”
Section: Introductionmentioning
confidence: 99%